The relationship between plasma total antioxidant capacity and dietary antioxidant status in adults with type 2 diabetes - Çapaş, Merve; Kaner, Gülşah; Soylu, Meltem; Inanc, Neriman; Başmısırlı, Eda (Progress in Nutrition, 2018)
Background and aim: There is limited information available on the association of plasma total antioxidant capacity (TAC) with dietary TAC in DM. The aim of this study was to evaluate the plasma TAC and its association with dietary antioxidant status in adults with Type 2 diabetes. Methods: Thirty outpatients diagnosed with type 2 DM (diabetics, n = 29) and 15 healthy subjects (control, n = 15) aged 40-70 with BMI≤ 30 kg/m2 were recruited to the study. Energy and nutrients intake, anthropometric measurements, dietary and plasma TAC, and some biochemical parameters were evaluated. The calculation of dietary TAC was based on previously published databases in which modified version of the FRAP. Results: Serum triglyceride, uric acid, and HbA1c levels in diabetics were higher than controls. A negative and statistically significant correlation was found between plasma TAC and HbA1c for diabetics. A negative and statistically significant correlation was observed between dietary TAC, HbA1c and fasting plasma glucose in diabetics. A positive and statistically significant correlation was found between plasma TAC and dietary intake of niacin in diabetics. No remarkable differences were found between dietary and plasma TAC in either group.Conclusion: This study provides evidence that dietary TAC is not an important modulator of antioxidant status in diabetic subjects. But, it showed that the increase in niacin and antioxidant taken with foods can be effective in controlling HbA1c and fasting plasma glucose.